Modeling and validation of multifield coupled self-sensing characteristics of magnetorheological elastomer for vibration isolators. (May 2022) - Li, Rui; Gou, Xin; Zhou, Mengjiao; Yang, Ping-an; Li, Penghua; Shou, Mengjie; Liao, Changrong; Wang, Xiaojie
Graphical abstract: Highlights: A high fidelity multifield coupled self-sensing model based on the magnetic-dipole behavior and the tunneling theory is proposed. The sensing and mechanical behaviors of MRE subjected to the combined effect of magnetic fields and mechanical loadings are studied. The proposed model is highly effective for predicting MRE isolator behaviors by comparing the measured data with theoretical results. Abstract: In this paper, a multifield coupled self-sensing model for magnetorheological elastomer (MRE) isolators is proposed. By dispersing carbonyl iron particles and multiwalled carbon nanotubes in polydimethylsiloxane, an MRE with improved force-sensing capability is fabricated as a further effort to explore its comprehensive sensing effect. Then, the model is developed based on magnetic dipole analysis and tunneling theory. In addition, the conductive mechanism and vibrational operating state of the MRE are analyzed, while the effects of input force and current are investigated. The experimental results show that the resistance of the MRE decreases with increasing force or current, which is consistent with the theoretical model. For instance, the resistance decreases from 1.55 kΩ to 0.55 kΩ as the force changes from 0 N to 160 N, and the dynamic resistance responses show a very good match with the force input curve and the response curve present continuous, stable, and perfectly reversible signals. The validation results demonstrate that the proposed model can reproduce experimental results well without causing significant differences. In summary, the proposed model provides an accurate approach to estimating the conductivity of MREs for self-sensing actuator applications.